Employee Performance in the Manufacturing Industry: Predictors of Rewards and Punishments - Suparman, Dadang; Rahayu, Siti Widhiyanti (International Journal of Business, Law, and Education, 2026)
Rewards are not about gifts or generosity, and giving punishment is clearly caused by indiscipline which can result in employee performance increasing, stagnating, or decreasing. Therefore, the aim of this research is to determine the effect of reward and punishment on employee performance in the manufacturing industry, in the Indonesian context. A quantitative method with a survey type was used to collect and estimate 114 respondent response data selected using a purposive sampling technique. Data analysis was verified with instrument tests, R2-based relationship prediction models, hypothesis testing with effect significance applied to the critical criterion of 1,96 at alpha 0,05, by adapting the regression model estimated using SPSS v.28. Research findings confirm that reward and punishment have a positive and significant effect on employee performance, both partially and simultaneously. However, rewards have moderate predictive power in explaining employee performance variance compared to punishment. These findings confirm that with the increasing complexity of organizational departments with various programs that present different challenges in the manufacturing industry, the management of reward and punishment programs that are fair, transparent and firm and implemented effectively, has the potential to make a positive contribution to improving employee performance which is relevant and can be applied in various companies.